The Holt Workbook - Martinez, Nancy C. (Orlando Holt, Rinehart and Winston, Inc., 1989)
You will learn to spend more time planning and revising your work than on making your first draft. You will learn the art of evaluating and and gain confidence in changing your own writing.
Keywords: Writing